Study on coarsening of Ag3Sn intermetallic compound in the Fe-modified Sn-1Ag-0.5Cu solder alloys - Shnawah, D.A.; Sabri, M.F.M.; Badruddin, I.A.; Said, S.M.; Bashir, M.B.A.; Sharif, Nu.M.; Elsheikh, M.H. (Elsevier, 2015)
The present study focuses on coarsening of Ag3Sn intermetallic compound in the Sn-1Ag-0.5Cu and Fe-modified Sn-1Ag-0.5Cu solder alloy. The investigations showed that the Ag3Sn intermetallics coarsened rapidly in the Sn-1Ag-0.5Cu solder alloy whereas the Ag3Sn intermetallics were found to be quite stable in the Fe-modified Sn-1Ag-0.5Cu solder alloy. The lattice strain in the Ag3Sn intermetallics and the blocking effect on Ag diffusivity in Sn matrix suggested the possible mechanisms for the coarsening suppression of the Ag3Sn intermetallics in the Fe-modified solder alloy. (C) 2014 Elsevier B.V. All rights reserved.